Short-term reduction of ankle spasticity after surgical lengthening of the triceps surae in chronic post-stroke patients: a retrospective cohort study - Galletti, Martina; Mazzoli, Davide; Zerbinati, Paolo; Rambelli, Chiara; Basini, Giacomo; Prati, Paolo; Mascioli, Francesca; Masiero, Stefano; Merlo, Andrea (Frontiers in Neurology, 2024)
Introduction In post-stroke patients with equinovarus foot deformity (EVFD), soft tissue rearrangements may contribute to muscle overactivity when a muscle is stretched or tension is applied. Therefore, we investigated the effects of surgically restoring the triceps surae (TS) length and lengthening ability on TS spasticity. Methods This retrospective study included chronic post-stroke patients who underwent neuro-orthopedic surgery inclusive of TS lengthening. TS spasticity was measured using the Modified Tardieu Scale (MTS) before and 1 month after surgery, both with the knee extended (KE) and flexed (KF). MTS variations were analyzed using the Wilcoxon test. The time from stroke onset was compared between patients with and without post-surgical spasticity using the t-test. Statistical significance was set at 5%. Results A total of 120 patients with EVFD, aged 57 (12) years, ranging from 1 to 36 years from stroke, were included in the study. The median MTS_KE score significantly decreased from 3 (range 0–4) to 2 (0–4) (p < 0.001) after surgery. The MTS score decreased by ≥1 point in more than half of the sample. Notably, 19 and 32 patients were completely relieved from spasticity (MTS = 0) in the KE and KF conditions, respectively. Post-surgical spasticity did not depend on the time since stroke onset (p = 0.560). Discussion TS lengthening led to a short-term reduction of spasticity in 41% and 63% of chronic post-stroke patients in the gastro-soleus complex and soleus, respectively, with complete relief observed in 21% and 30% of the sample. Surgical lengthening can be considered an effective treatment that not only restores joint range of motion but also may reduce spasticity, even in chronic patients.